The Application of Roleplay in Improving Students' Speaking Ability - Egeten, Yericho Christian; Tuerah, Ignatius J. C.; Hampp, Paula A. (Program Studi Pendidikan Bahasa Inggris, 2024)
This study raises a problem that occurs in SMA Negeri 1 Tenga, which is the difficulties experienced by students while learning English, especially on speaking ability. As for some students who still have difficulty to speak in english and it makes them difficult to expressing their ideas in English. This research was conducted to examine eleventh grade of Science Program students at SMA Negeri 1 Tenga. This study aims to find out that the student speaking ability could be improve by using roleplay as learning model. The research used was one group pretest-posttest design. The research design of the one group pre test and post test design was measured using the pre test carried out before being given the treatment and the post test which was carried out after given treatment. The instrument used is a test. The population in this study were 20 students of class XI Science Program SMA Negeri 1 Tenga. The results showed that the pre-test score of all students was 975, with an average score of 48.75, while the post-test score was 1215 with an average of 61. These results indicate that students' speaking ability has improved after using roleplay, so that the application of roleplay is effective in improving students' speaking ability. Therefore, roleplay can be recommended as a learning model that can be used to improve students' speaking ability.